War and the Development of Cardiac Surgery - Kamruzzaman, M; Amin, F; Hosain, SN (Cardiovascular Journal, 2012)
Despite all the devastating effects, wars have made some very significant positive impact in the development of cardiac surgery. Heart is an organ that cannot be stopped even for a minute, there by making it very difficult for the surgeons to operate. The wars of the Twentieth Century, particularly the two Great wars produced a significant number of patients with heart injury to reach surgeons operating tables. This gave the surgeons a unique opportunity to study, operate, practice and research cardiac surgical patients. Notable names including Wilfred Bigelow, Walton Lillehei, John Gibbon, Christian Cabrol, Vasilii Kolessov and Alexander Vishnevsky all were world war veterans and utilized their wartime experience later on in the development of cardiac surgery. Had there not been the two great wars, the development of cardiac surgery would have been delayed probably by years. DOI: http://dx.doi.org/10.3329/cardio.v4i2.10463 Cardiovasc. j. 2012; 4(2): 174-178